Putative deletions of the proximal heterochromatin of chromosome three in Drosophila melanogaster - Baldwin, Madeline Carol (University of British Columbia, 2011)
The term, heterochromatin, refers to those portions of a chromosome which stain very darkly early in the division cycle at a time when most of the chromosomal material stains very lightly. After the discovery of the mutagenic effects of X-rays, large numbers of mutants were recovered in Drosophila. These mutants were genetically mapped but none of them seemed to be located in the heterochromatic regions of the chromosomes. This observation led to the hypothesis that heterochromatin was genetically inert. Since then the problem of the function of heterochromatin has engaged the attention of many different researchers. One of the few mutants known to reside in the proximal heterochromatin of the X chromosome is bobbed. Ritossa and Spiegelman (1965) have presented evidence that bobbed is the nucleolus organizer, the site of ribosomal RKA synthesis. Their results suggest that this is a highly redundant region of the chromosome. If heterochromatin in general is greatly redundant, this would offer one explanation for the apparent lack of genetic loci. A mutant phenotype might result only after large blocks of the chromosome have been deleted. A scheme involving the use of attached-autosomes to select for those third chromosomes which have sustained breaks in the proximal heterochromatin was devised. In general, virgin females were irradiated and attached-third chromosomes were selected for by mating these females to attached-third males. Female progeny carrying these newly synthesized attached-autosomes are, in turn, irradiated and newly reconstituted chromosomes were selected for by mating the females to males carrying normal third chromosomes. Thus, each newly reconstituted chromosome has sustained a number of breaks at different positions in the proximal heterochromatin. Using this procedure, we recovered sixty-six homozygous lethal chromosomes. Fifty-three of these sixty-six lethals may be placed in one of the six complementation groups, two of which appear to be multisite deletions. In addition, these fifty-three lethals appear to be located, by the results of genetic mapping, in the region spanning the centromere. These two pieces of evidence suggest that the method used here does, indeed, select for deletions in the proximal heterochromatin. === Science, Faculty of === Zoology, Department of === Graduate